Peer Interaction in School as a Mediator Between Adolescent Self-Esteem and Coping Strategies - Muarifah, Alif; Oktaviani, Fitriana (Humanitas: Indonesian Psychological Journal, 2025)
Coping strategies help manage stress in challenging social contexts, especially for adolescents facing unique developmental challenges. Their effectiveness depends on context, individual traits, social responses, and sociocultural factors. This study aimed to examine the model of adolescents’ coping strategies in the social context, viewed from the peer interaction in school, affected by adolescents’ self-esteem. 530 senior high school students were involved as participants. There were 245 male students and 285 female students aged between 15 and 18 years old (M= 16.52, SD=0.673) in five schools in Bantul. Coping strategy, peer interaction, and self-esteem scales were developed to collect data. Data were analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS 4. The model exhibited a good fit and showed that adolescents’ coping strategies were affected by self-esteem and mediated by peer interaction. This study demonstrated the significant effect of self-esteem on peer interactions among adolescents. Adolescents may possess a good coping strategy when having good peer interaction and self-esteem. Further findings indicate that most participants’ problem-focused and emotion-focused coping strategies, peer interaction, and self-esteem were categorized as the low and high category. However, the low category of each variable needs to be considered